How and when is family dysfunction associated with adolescent mobile phone addiction? Testing a moderated mediation model. (April 2020) - Liu, Qing-Qi; Yang, Xiu-Juan; Hu, Yu-Ting; Zhang, Chen-Yan; Nie, Yan-Gang
Highlights: Family dysfunction was positively correlated with mobile phone addiction among Chinese adolescents. Social anxiety acted as a mediator. The direct and indirect effects were moderated by mindfulness. Abstract: Mobile phone addiction has gained much research attention. Previous studies have primarily focused on college students, while there have been numerous calls for efforts to better understand mobile phone addiction in adolescents. Moreover, previous research has mainly focused on individual factors of mobile phone addiction; however, less is known about the effect of family factors and the underlying mechanisms. The present study tested the effect of family dysfunction on adolescent mobile phone addiction and explored how and when family dysfunction was associated with adolescent mobile phone addiction. A cross-sectional questionnaire survey regarding family dysfunction, mobile phone addiction, social anxiety, and mindfulness was administered to 1020 Chinese adolescents. Results showed that social anxiety partially mediated the association between family dysfunction and mobile phone addiction. In addition, both the direct association between family dysfunction and mobile phone addiction and the indirect association through social anxiety were moderated by mindfulness. These two links were weaker for adolescents with high mindfulness than for those with low mindfulness. The present study extends previous research by linking family dysfunction to adolescent mobile phone addiction and uncovering how and when family dysfunction is associated with adolescent mobile phone addiction. These results have important implications for the prevention and intervention of adolescent mobile phone addiction.